Uwagi na temat etyki normatywnej: [Remarks on normative ethics] (Studia Prawnicze / The Legal Studies, 1985)
The author presents his concept of normative ethics which assumes that no ethical rule may be considered binding:a) unless it assumes that the individual is free to formulate his behaviour (for which everybody is responsible only to himself), b) in relation to behaviour interfering with the autonomy of another person requires that everybody should be responsible for his behaviour irrespective of the principle according to which such behaviour has been chosen. In connection with those assumptions the author introduces a number of notions which are to help to construct such ethics. They are: natural admissibility and inadmissibility of behaviour, conditions defining social duties, activity of the state as a means of influencing human behaviour through sanctions